NAKHON SI THAMMARAT MUSLIM BUSINESS CLUB: MANAGING DA'WAH AND ENTREPRENEURSHIP AMONG MUSLIM MINORITIES IN THE SOUTHERN THAILAND - Kusuma, Bayu Mitra A. (Jurnal Ilmiah Syi'ar, 2020)
Pattani is not a single representation of the Islamic existence in Thailand,because in reality Muslim societies have been living in various regions. Oneplace where Muslim societies can form new identities is in the Nakhon SiThammarat province, where they are able to transform into an adaptive andhighly competitive group. To examine more deeply this phenomenon, this studyuses a type of qualitative research with a descriptive approach, and emphasizesthe interactive data analysis of the Miles and Huberman models. The results offield research show that one of the manifestations of Muslim existence is toestablish Nakhon Si Thammarat Muslim Business Club (NMBC). In itsexistence, NMBC has two main functions: First, to bridge and unite the power  of Muslim entrepreneurs from micro to large scale. Secondly, to become a da’wah institution on Islamic philanthropy based on the belief that the more charity, the more business will develop. NMBC gives direction to the development of Muslim entrepreneurship in two ways: First, positioning the majority group as partners, not competitors. Second, to strengthen the Blue Ocean strategy in which Muslim entrepreneurs must find new business sector gaps that are not controlled by the majority group.